Relations in Virtual Performing Art Activities in the Time of Crisis - M.A. Haris Firismanda (Universitas Brawijaya, 2022)
This study focuses on describing the relationships in virtual spaces as a result of the impact of the changes in the pandemic. The changes are in terms of activities carried out by the Student Activity Unit of Matapena of Faculty of Cultural Studies, Universitas Brawijaya (henceforth, FCS UB) in virtual spaces. In this case, there were some adaptations carried out by the organization. By applying a theory by Marvin Harris about Cultural Materialism, this study revealed the mode of production in the form of changes that affect the social structure. In addition, the changes also influenced the community consumers in cultural materialism. By using an ethnographic method, it observed their adaptation process. The results of this study showed that there was a process of changing cultural ethics during virtual performing art activities and there were various kinds of adaptations made to certain conditions. Moreover, material needs during the activities were also tailored to the conditions at the time of crisis. Despite these changes, they did not remove the essence of the events in the virtual spaces.